Research progress of chaotic secure optical communication - Lilin YI; Junxiang KE (Tongxin xuebao)
For the key technologies and latest research progress on chaotic secure optical communication,chaos generation methods based on different nonlinear components were introduced firstly.Then the research progress of chaotic optical communication was discussed,including how to improve the security level,and how to increase the transmission capacity and distance of chaotic optical communication.At last,the limitations and potentials of chaotic optical communication were discussed,the key technologies and research progress of chaotic secure optical communication were summarized.